Adjunctive Use of Melatonin in Pediatric Urinary Tract Infections: A Randomized Controlled Trial: Use of Melatonin in UTIs - Arjmand Shabestary, Ali; Dorreh, Fatemeh; Yousefichaijan, Parsa; Rafiei, Mohammad; Azodzaade Ardakani, Amirvali; Toghra, Alireza (Journal of Pediatric Nephrology, 2026)
Background and Aim: Urinary tract infections (UTIs) are among the most common bacterial infections in children and adolescents. Despite standard antibiotic therapy, symptom resolution can be delayed due to ongoing inflammation. Melatonin, a neurohormone with known antioxidant and immunomodulatory properties, may offer therapeutic benefits in this context. This study aimed to evaluate the clinical efficacy of adjunctive melatonin therapy in pediatric patients with UTIs, focusing on symptom resolution and potential anti-inflammatory effects. Methods: In this double-blind, randomized, placebo-controlled trial, 100 children aged 4–18 years with confirmed UTI and concurrent sleep disturbances were assigned to receive either melatonin (3 mg/day) plus antibiotics (intervention group) or antibiotics plus placebo (control group) for 10 days. Primary outcomes included time to resolution of fever, dysuria, abdominal pain, urinary frequency, and incontinence. Results: Baseline characteristics were similar between groups. The melatonin group showed significantly faster resolution of fever (1.3±0.49 vs 3.7±0.69 days, P=0.001), abdominal pain (1.2±0.54 vs 3.62±0.67 days, P=0.001), and dysuria (1.5±0.57 vs 3.6±0.67 days, P=0.001). No significant differences were observed in urinary frequency or incontinence outcomes. No adverse effects related to melatonin were reported. Conclusion: Adjunctive melatonin therapy appears to accelerate the resolution of key UTI symptoms in children when combined with antibiotics, likely due to its anti-inflammatory and antioxidant properties. These findings suggest a potential role for melatonin in pediatric UTI management and warrant further investigation in larger, multicenter trials.